Fabrication and optimization of phospholipids-based phase separation in-situ gel loaded with BMP-2 nanosized emulsion for bone defect - Mohammed Alissa; Ahmed Hjazi; Ghadah S. Abusalim; Ghfren S. Aloraini; Suad A. Alghamdi; Waleed Y. Rizg; Waleed Y. Rizg; Khaled M. Hosny; Khaled M. Hosny; Deena M. Bukhary; Hanaa Alkharobi (Frontiers Media S.A., 2023)
Introduction: The health, development, and/or survival of a newborn can be impacted by congenital abnormalities such as cleft lip (CLP) and palate, one of alveolar bone defects that emerge thru pregnancy. Therefore, the primary purpose of this study is to use phospholipids-based phase separation in-situ gel (PPSG) in combination with bone morphogenetic protein-2 nanoemulsion (BMP-2-NE) to aid repairing alveolar bone defects.Methods: To investigate how formulation parameters, such as the concentrations of BMP-2 aqueous solution, LauroglycolTM FCC, and Labrafac PG oil, affect NE qualities including droplet size and stability index, an l-optimal co-ordinate exchange statistical design was opted. Injectable PPSG with the best NE formulation was tested for viscosity characteristics, gel strength, water absorption, and in-vitro BMP-2 release. In rabbits, the percentage of BMP-2 that was still in the maxilla after 14 days was assessed.Results: Collected results revealed that the droplet size and stability index of optimal NE were discovered to be 68 2.0 nm and 96 1.3%, respectively. When mixed with water, optimal BMP-2 NE loaded PPSG became viscous and reached a gel strength of 41 s, which is adequate for injectable in-situ gels. In comparison to BMP-2 solution loaded in-situ gel, the in-vivo studies indicated that the newly created BMP-2 NE loaded PPSG produced a sustained and controlled release of BMP-2 that continued for 336 h (14 days). Further, 8% of the BMP-2 was still entrapped and not completely dissolved after 14 days, thus, created formulation allowed a higher percentage of BMP-2 to remain in rabbits' maxilla for longer time.Conclusion: PPSG that has been loaded with BMP-2 NE may therefore be a promising, fruitful, and less painful paradigm for the noninvasive therapy of CLP with significant effect and extended release.